2017
DOI: 10.1007/s12032-017-1020-4
|View full text |Cite|
|
Sign up to set email alerts
|

Ten-year results of accelerated hypofractionated adjuvant whole-breast radiation with concomitant boost to the lumpectomy cavity after conserving surgery for early breast cancer

Abstract: Accelerated hypofractionated whole-breast radiotherapy (WBRT) is considered a standard therapeutic option for early breast cancer (EBC) in the postoperative setting after breast conservation (BCS). A boost to the lumpectomy cavity may further increase local control. We herein report on the 10-year results of a series of EBC patients treated after BCS with hypofractionated WBRT with a concomitant photon boost to the surgical bed over 4 weeks. Between 2005 and 2007, 178 EBC patients were treated with a basic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Many published clinical experiences with H‐SIB have been reported, 12,19‐23 but these usually have short follow‐up and few have been compared with C‐SIB. Acute toxicity of H‐SIB was mild 24‐27 and slightly lower than in HF with sequential boost (H‐SEQ), 28 C‐SIB 27,29,30 or CF with sequential boost (C‐SEQ) 26,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Many published clinical experiences with H‐SIB have been reported, 12,19‐23 but these usually have short follow‐up and few have been compared with C‐SIB. Acute toxicity of H‐SIB was mild 24‐27 and slightly lower than in HF with sequential boost (H‐SEQ), 28 C‐SIB 27,29,30 or CF with sequential boost (C‐SEQ) 26,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors indicated long‐term overall survival rates between 77% and 94% in patients underwent BCS followed by standard radiotherapy with or without boost . Despite the high ipsilateral breast cancer recurrence found in our study, the 10‐year overall survival of 82.8% was in accordance with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…521 articles were found, of which 83 articles were found to be relevant. Ten of these studies are prospective trials, and medium to long-term outcomes have been reported for seven (20)(21)(22)(23)(24)(25)(26). These are summarized below.…”
Section: Simultaneous Integrated Boost (Sib)mentioning
confidence: 99%